2021
DOI: 10.1177/07356331211036492
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Lab in Immersive VR—An Embodied Approach to Training Wafer Preparation

Abstract: This paper reports an immersive virtual reality lab (iVRLab) training environment that offers college students an immersive and embodied experience in engineering lab work. The iVRLab provides a simple and safe environment for students to learn the complex lab operations to process and prepare silicon wafers. It features highly embodied interactions congruent to the actual body movements to manipulate the lab devices and materials in the physical world. Fourteen college students participate the lab training an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Through hands-on, students comprehended and constructed learning impressions in the implementation process to deepen their cognition and avoid being unable to acquire and apply the technology by simply reciting theories from books. From the experiment of STEM robot coding, Xu and Wang (2022) concluded that teaching with different types of STEM activities would result in junior and senior high school students maintaining a positive tendency to STEM. Besides, students with highly positive STEM tendencies might be more interested in STEM-related jobs in the future.…”
Section: Extended Reality and Stem Educationmentioning
confidence: 99%
“…Through hands-on, students comprehended and constructed learning impressions in the implementation process to deepen their cognition and avoid being unable to acquire and apply the technology by simply reciting theories from books. From the experiment of STEM robot coding, Xu and Wang (2022) concluded that teaching with different types of STEM activities would result in junior and senior high school students maintaining a positive tendency to STEM. Besides, students with highly positive STEM tendencies might be more interested in STEM-related jobs in the future.…”
Section: Extended Reality and Stem Educationmentioning
confidence: 99%
“…Therefore, after learners have acquired the basic knowledge, they cannot simply exploit this knowledge in the actual experimental field. They must instead use their imagination to simulate a real experimental field, which can lead to a lack of confidence in learners who finally step into the real experimental field (Saab et al, 2021; Xu & Wang, 2021). In addition, during a hands‐on experiment, a lack of teachers may make it difficult for learners to solve their problems immediately, leading to anxiety during the long wait for assistance, with the result in interrupted, failed experiment (Barron et al, 2021; Pimentel & Kalyanaraman, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some researchers introduced VR applications in simulating medical emergencies and in training medical and nursing students about dissection and other clinical practices (Adamovich et al 2009 ; Andersen et al 2018 ; Chang and Weiner 2016 ; Cho et al 2013 ; Smith and Hamilton 2015 ; Sugden et al 2012 ). In the social science sectors like in the education field, people are also conducting research in VR-based educational scenarios, such as teaching and training, for a variety of students and learners (e.g., Bouta and Retalis 2012 ; Ke et al 2020 ; Vesga et al 2021 ; Xu and Wang 2021 ). Carefully designed scenarios in VR also help people with special needs.…”
Section: Introductionmentioning
confidence: 99%